Response of Plant Distance to Wards Growth and Production Cayenne pepper (Capsicum frutescens L.) - Ali, Akhmad; Sangadji, Zulkarnaim; Sangadji, Ismail Munadi (Agrikan Jurnal Agribisnis Perikanan, 2024)
This chilli plant, with various constraints on the area for planting, to increase the production of cayenne pepper plants can use a spacing that is in accordance with the recommended instructions which will have ecological and economic benefits, besides that vegetable pesticides made from active living organisms can function as inhibiting certain nutrients or facilitating the availability of nutrients in the soil for cayenne pepper (Capsicum frutescens L.). Spacing is one of the many factors that affect chili production. Increasing the production of cayenne pepper plants can be done by improving the level of planting density. To increase the yield of cayenne pepper, in addition to spacing and the use of organic and inorganic fertilizers, farmers must know for sure about the dose of spraying the first dose of fertilizer and spraying the next fertilizer.